A Comparative Analysis between Laparoscopic and Open Adhesiolysis at a Tertiary Care Center. Issue 3 (March 2014) - Davies, Stephen W.; Gillen, Jake R.; Guidry, Christopher A.; Newhook, Timothy E.; Pope, Nicolas H.; Hranjec, Tjasa; Sawyer, Robert G.; Hallowell, Peter T.
Laparotomy has been the favored approach regarding surgical management of small bowel obstruction (SBO); however, laparoscopy may offer improved outcomes. Patients undergoing laparoscopic lysis of adhesions (LOA) at our institution for SBO will have lower postoperative morbidity and 30-day mortality. Patients undergoing LOA at our institution, from 2000 to 2011, were reviewed. Categorical data were analyzed with χ 2 or Fisher's exact tests. Continuous data were analyzed with Student's t test or Wilcoxon rank sum. One hundred two (38 laparoscopic, 64 open) LOA cases were selected. Perioperative contamination and conservative management were higher in the open group. Open cases had a greater incidence of intensive care unit (ICU) admissions and longer length of stay. Stratified analysis determined a strong association between perioperative contamination and a higher incidence of ICU admission, perioperative contamination and longer LOS, and conservative management and longer LOS. Finally, patient outcome did not differ between those treated by surgeons trained in minimally invasive surgery (MIS) compared with those not trained in MIS. Careful consideration of surgical approach and timing is called for in all patients with SBO; however, whenever possible, laparoscopic preference should be given to most patients in an expeditious fashion irrespective of MIS training.